Cardiac and inflammatory biomarkers in perinatally HIV-infected and HIV-exposed uninfected children. (19th June 2018) - Wilkinson, James D.; Williams, Paige L.; Yu, Wendy; Colan, Steven D.; Mendez, Armando; Zachariah, Justin P.V.; Van Dyke, Russell B.; Shearer, William T.; Margossian, Renee E.; Lipshultz, Steven E.
Abstract : Objectives: To compare distributions of serum cardiac and inflammatory biomarkers between perinatally HIV-infected (PHIV) and perinatally HIV-exposed uninfected (PHEU) children, to evaluate their associations with echocardiographic measures, and among PHIV youth, with antiretroviral therapy (ART) and HIV disease severity measures. Design: Cross-sectional analysis of temporally paired serum samples for biomarkers and echocardiograms in a prospective multicenter cohort study of PHIV and PHEU youth. Methods: Serum samples were analyzed among 402 youth in the PHACS Adolescent Master Protocol (AMP) for high-sensitivity cardiac troponin-T (hs-cTnT, a cardiomyocyte injury marker), N-terminal-pro-brain natriuretic peptide (NT-proBNP, a myocardial stress marker), and inflammatory markers [high-sensitivity C-reactive protein, interleukin (IL)-1, IL-6, IL-8, IL-10, IL-18, tumor necrosis factor-α (TNF-α), and soluble TNF receptor II (sTNF-RII)]. Echocardiograms were centrally measured and parameters converted to z cores to account for differences in age and body size. Results: Compared with PHEU ( N  = 156), PHIV youth ( N  = 246) more often had detectable hs-cTnT and higher levels of sTNF-RII and IL-18. Higher inflammatory biomarkers were generally associated with higher left ventricular (LV) wall stress and lower LV function and LV mass in the two groups. Among PHIV youth, the biomarkers were more strongly associated with current rather than historical immunologic and virologic status. Conclusion: PHEU and PHIV have modest, significant differences in serum levels of specific inflammatory and active myocardial injury biomarkers. Higher biomarker levels were associated with lower LV mass and shifts in LV structure. Further study is warranted on the longitudinal role of cardiac and inflammatory biomarkers for targeting interventions among PHIV and PHEU youth. Abstract : Supplemental Digital Content is available in the text